PSMA targeting in metastatic castration-resistant prostate cancer: where are we and where are we going? - Anne-Laure Giraudet; David Kryza; Michael Hofman; Aurélie Moreau; Karim Fizazi; Aude Flechon; Rodney J. Hicks; Ben Tran (Therapeutic Advances in Medical Oncology, 2021)
Prostate-specific membrane antigen (PSMA) is highly expressed on the membrane of most prostate cancer cells and to a lesser extent in normal tissues. Many vectors targeting this protein have been created over the past decade and numerous clinical studies have positively demonstrated the tolerance and efficacy of radiolabeled prostate-specific membrane antigen ligands for PSMA radioligand therapy (PRLT). Preliminary results are encouraging that PRLT will become an important addition to the current therapeutic options in a number of settings. Improvement in radiopharmaceutical targeting and combination with other oncological agents are under investigation to further improve its therapeutic efficacy. These encouraging results have led to the development of other therapies using PSMA as a target, such as PSMA–targeted chimeric antigen receptor T-cells, PSMA–targeted antibody drug conjugates, and PSMA–targeted bi-specific T-cell-directed therapy. This narrative review details the current state and advancements in prostate-specific membrane antigen targeting in prostate cancer treatment.